Approaching the domesticated plant holobiont from a community evolution perspective. Issue 5 (17th May 2022) - Soldan, Riccardo; Fusi, Marco; Preston, Gail M.
Abstract : Plants establish a pivotal relationship with their microbiome and are often conceptualized as holobionts. Nonetheless, holobiont theories have attracted much criticism, especially concerning the fact that the holobiont is rarely a unit of selection. In previous work, we discussed how the plant microbiome can be considered to be an 'ecosystem on a leash', which is subject to the influence of natural selection acting on plant traits. We proposed that in domesticated plants the assembly of the plant microbiome can usefully be conceptualized as being subject to a 'double leash', which encompasses both the effect of artificial selection imposed by the domesticator on plant traits and the leash from the plant to the microbiome. Here we approach the domesticated plant holobiont, simply defined as a community of organisms, from a community evolution point of view, and show how community heritability (a measure of community selection) complements the 'double-leash' framework in providing a community-level view of plant domestication and its impact on plant–microbe interactions. We also propose simple experiments that could be performed to investigate whether plant domestication has altered the potential for community selection at the holobiont level.